MURAL KAMPUNG BANTARAN KALI BORO: PEMBERDAYAAN KAMPUNG MELALUI KEGIATAN KESENIAN - handayani, endang sri; fuad, figur rahman (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2019)
Kampung as the important factor the culture of a city plays important role in teh city develpoment. The community movements in managing their environment has become an interesting thing to discuss. This reserach is a qualitative study on the comunity creativity residing in Kali Boro riverside. It exproses the activities that the community caries in managing their environment through art. The data are collected trough interview and literatures. The results of this research shows that art can attract the community in Kali Boro riverside to actively participate in the environment improvement and trigger their creativity. Keywords: Kampung, creativity, art.